Mulberry and cherry anthocyanin consumption prevents oxidative stress and inflammation in diet‐induced obese mice. Issue 3 (7th January 2016) - Wu, Tao; Yin, Jinjin; Zhang, Guohua; Long, Hairong; Zheng, Xiaodong
Abstract : Mulberry and cherry anthocyanin (MA, CA) consumption prevents oxidative stress and inflammation in diet‐induced obese mice. Consumption of CA and MA at 200 mg/kg food reduced bodyweight gain by 29.6 and 32.7%, respectively, in HFD‐fed C57BL/6 mice. CA and BA supplementation could effectively improve the lipid profiles, decrease serum glucose and leptin levels, reduce MDA production, increase SOD and GPX activities, and down‐regulate the expression of the TNFα, IL‐6, iNOS, and NF‐кB genes. Therefore, MA and CA can potentially alter bodyweight by alleviating oxidative stress and inflammation in diet‐induced obesity. Abstract : Scope: This study aimed to determine whether cherry anthocyanin (CA) and mulberry anthocyanin (MA) can alleviate oxidative stress and inflammation associated with developing obesity in mice fed with high‐fat diet (HFD). Methods and results: CA and MA were added in the daily food of mice throughout the experiment. Sixty mice were randomly divided into two groups: a low‐fat diet (LFD, n = 12) group and HFD ( n = 48) group. Mice in the HFD group were supplied with a HFD for 8 wks to induce obesity. The HFD‐fed mice were then divided into four subgroups for another 8‐wk experiment. The subgroups included the control group, HFD plus Orlistat group, and HFD plus CA or MA group, with each group consisting of 12 mice. Consumption of CA and MA at 200 mg/kg food reduced bodyweight gain by 29.6 and 32.7%, respectively, in HFD‐fed C57BL/6 mice. CA and MA supplementation could effectively improve the lipid profiles, decrease serum glucose and leptin levels, reduce MDA production, increase SOD and GPX activities, and down‐regulate the expression of the TNFα, IL‐6, iNOS, and NF‐кB genes. Conclusion: Therefore, MA and CA can potentially alter bodyweight by alleviating oxidative stress and inflammation in diet‐induced obesity.